Maternal sepsis. Issue 1 (May 2022) - Filetici, Nicoletta; Van de Velde, Marc; Roofthooft, Eva; Devroe, Sarah
Abstract : Maternal sepsis is a life-threatening condition defined as organ dysfunction resulting from infection that can arise during pregnancy, childbirth, postabortion, or in the postpartum period. Validated diagnostic criteria of maternal sepsis and septic shock may reduce the impact of this condition on maternal health worldwide, but the lack of consensus on adequate tools due to the overlap between physiological adaptations that occur during pregnancy and signs and symptoms of infection and sepsis can delay both diagnosis and treatment. In the absence of evidence-based guidelines for obstetric populations, the WHO recommends the use of the "Surviving Sepsis Campaign" sepsis protocols for maternal care adapted to the local obstetric population. Interventions within the first hour from diagnosis have been proposed in 2021 to emphasize the state of emergency of a maternal sepsis. This review will highlight the utility of standardized diagnostic criteria, the implemented approaches for the prevention and treatment of maternal infections, and the strategies for early management of critically ill parturients.